2004
DOI: 10.1128/jvi.78.23.12857-12867.2004
|View full text |Cite
|
Sign up to set email alerts
|

A Cyclin-Binding Motif within the Amino-Terminal Homology Domain of EBNA3C Binds Cyclin A and Modulates Cyclin A-Dependent Kinase Activity in Epstein-Barr Virus-Infected Cells

Abstract: The Epstein-Barr virus (EBV) nuclear antigen 3C (EBNA3C) is a virus-encoded latent antigen essential for primary B-cell transformation. In this report we demonstrate that although the carboxy terminus of EBNA3C predominantly regulates cyclin A-dependent kinase activity, the region of greatest affinity for cyclin A lies within the EBNA3 amino-terminal homology domain of EBNA3C. Detailed mapping studies employing both in vitro binding assays and coimmunoprecipitation experiments implicated a small region of EBNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
73
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(77 citation statements)
references
References 30 publications
3
73
1
Order By: Relevance
“…Previous studies have demonstrated the ability of EBNA3C to target cell cycle regulators, resulting in the deregulation of the mammalian cell cycle (21)(22)(23)(24)32). EBNA3C targets the key cell cycle regulators p27 and pRb by recruiting components of the SCF Skp2 ubiquitin ligase and facilitating the degradation of these inhibitors of the mammalian cell cycle (21,23).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have demonstrated the ability of EBNA3C to target cell cycle regulators, resulting in the deregulation of the mammalian cell cycle (21)(22)(23)(24)32). EBNA3C targets the key cell cycle regulators p27 and pRb by recruiting components of the SCF Skp2 ubiquitin ligase and facilitating the degradation of these inhibitors of the mammalian cell cycle (21,23).…”
Section: Discussionmentioning
confidence: 99%
“…Using pulse-chase experiments, we show that EBNA3C can stabilize c-Myc. This domain of EBNA3C also recruits and modulates the activity of pRb and p27, both major regulators of the mammalian cell cycle (21)(22)(23)(24). The inclusion of c-Myc in the group of proteins modulated by this region further demonstrates the importance of this region of EBNA3C in regulating the cell cycle in EBV infections.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies have demonstrated that EBNA3C targets cell cycle regulators, resulting in deregulation of the mammalian cell cycle (3,20,21,32,33). EBNA3C manipulates the Rb-E2F axis in reporter assays and in rat fibroblast transformation experiments (32).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, all mutations in EBNA3A or EBNA3C that inhibit association with RBPJ are null for LCL growth (22)(23)(24), whereas EBNA3A or EBNA3C mutations that affect binding to the adenovirus E1a C-terminal binding protein (CtBP) corepressor result in continuous, albeit slower, growth (22)(23)(24)(25)(26). EBNA3C or EBNA3A have many specific and potentially significant interactions with other transcription factors or modifiers, including PU.1, Spi-B, HDAC1, DP103, prothymosin-α, p300, Nm23-H1, SUMO1, and SUMO3, cyclin A, SCF SKP2 ubiquitin ligase, pRb, Chk2, Mdm2, and MRS18-2, and these interactions could be relevant to CDKN2A p16 INK4A or p14 ARF regulation and LCL growth (27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38). Furthermore, EBNA3C upregulates TCL1A and ITGA4, down-regulates JAG1 and NCALD RNAs, and cooperates with EBNA3A in repressing Bim, a proapoptotic Bcl-2 family protein (24,(39)(40)(41).…”
mentioning
confidence: 99%